ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESA (KPRI) UNIVERSITAS RIAU DI PEKANBARU - Yani Diana Betri; Gusnardi '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to to know and analyse monetary performance of Co-Operation Officer Of Republic Of Indonesia (KPRI) University of Riau in Pekanbaru if seen from his monetary ratio of year 2012, 2013 and 2014. This Research place is executed in Co-Operation environment Officer Of Republic Of Indonesia (KPRI) University of Riau in Pekanbaru. This Research is started from May up to October month 2015. As for this research type is quantitative descriptive research, that is explaining result of research which in the form of coresponding financial statement data to monetary performance of co-operation. Source of data of this research is obtained data of Responsibility Reporting of[is Official Member Of Co-Operation Officer Of Republic Of Indonesia (KPRI) University of Riau Year 2012, 2013 and 2014. As for used data collecting technique that is with study method of survey. Result of research indicate that monetary performance of Co-Operation Officer Of Republic Of Indonesia University of Riau (KPRI) of year 2012 until year 2014 have goodness. This matter because of condition of Ratio of Likuiditas, Solvency Ratio and Ratio Profitability which consist of Net Profit Margin (NPM), Gross of Profit Margin ( GPM) and of Return On Investment (ROI) continue to experience of the make-up of from year of to year.Keywords: Ratio of Likuiditas, Solvency Ratio, Ratio Profitability and Monetary Performance.